2020
DOI: 10.5195/ijms.2020.740
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction and Its Relationship with Depression and Academic Performance: A Cross-Sectional Study at a Medical School in Pakistan

Abstract: Background: Excessive Internet use may induce depression, influence relationships, and decrease academic performance. There is scarce information about Internet addiction in Pakistan. This study aimed to determine prevalence of Internet addiction and its relationship with depression and academic performance. Methods: A study based on a self-administered survey was carried out at a medical school in Peshawar, Pakistan. Participants were medical students (MBBS) and a non-randomized convenience sampling tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…[ 14 ] A significantly positive correlation of internet addiction with depression, anxiety, and stress was evident in the present study, the finding supported by various other authors in their respective studies. [ 15 16 17 ] A few other studies also reported that internet addiction is associated with loneliness, depression, anxiety, stress, and low self-esteem. [ 18 19 20 ] Another study conducted among medical students in Delhi concluded a strong correlation between internet addiction, disturbed sleep quality, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] A significantly positive correlation of internet addiction with depression, anxiety, and stress was evident in the present study, the finding supported by various other authors in their respective studies. [ 15 16 17 ] A few other studies also reported that internet addiction is associated with loneliness, depression, anxiety, stress, and low self-esteem. [ 18 19 20 ] Another study conducted among medical students in Delhi concluded a strong correlation between internet addiction, disturbed sleep quality, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to our experience, university students are one of the most at-risk groups especially for the following reasons (cf. Ceyhan, 2011;Salehi et al, 2013;Skarupova and Blinka, 2015;Chraska, 2019, Ansar et al, 2020):…”
Section: Discussionmentioning
confidence: 99%
“…Internet addiction in adolescence can have multiple negative impacts including cognitive problems (Park et al, 2011 ), loneliness (Hasmujaj, 2016 ), poor family and interpersonal relationship problems (Seo et al, 2009 ; Hou et al, 2019 ) poor school performance (Javaeed et al, 2020 ; Hamza, 2021 ), lower self-esteem (Yedemie, 2021 ), lack of selfcare (Tran et al, 2017 ), depression (Ha et al, 2007 ; Guo et al, 2012 ; Iskender, 2014 ; Ansar et al, 2020 ), anxiety stress (Silvia Kratzer1, 2007 ; ElSalhy et al, 2019 ; Saikia et al, 2019 ; Boudabous et al, 2020 ), and obesity (Bozkurt et al, 2018 ; Arafa et al, 2020 ; Citlik-Saritas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%